Analysis of environment response effects on excitation energies within subsystem‐based time‐dependent density‐functional theory. Issue 21 (1st April 2020) - Scholz, Linus; Tölle, Johannes; Neugebauer, Johannes
Abstract: We analyze the ability of subsystem time‐dependent density‐functional theory (sTDDFT) to describe environmental response effects. To this end, we utilize the recently proposed "exact" version of sTDDFT relying on projection‐based embedding (PbE), which so far was applied only for the special case of two subsystems. We confirm that PbE‐sTDDFT in combination with supersystem bases yields results equivalent to those of supermolecular TDDFT calculations for systems solvated by many solvent molecules, using the previously studied system of methylene‐cyclopropene⋯(H2 O)17 as an example. By means of this exact reference embedding framework, we are able to disentangle solvent effects introduced in terms of the embedding potential from those caused by solvent response couplings, both for the PbE variant and for sTDDFT with approximate non‐additive kinetic energy functionals. Furthermore, we show that the use of a monomer basis introduces significant errors for the environmental response contribution. Employing a virtual‐orbital localization strategy on top of PbE‐sTDDFT, we can also directly assess the impact of inter‐subsystem charge‐transfer excitations on the entire solvent effect, which turn out to play a significant role for the environmental response. Finally, we analyze the response effects introduced by the individual solvent molecules and their interdependence, and show that a simple, pair‐wise additive correction for solvent response yields excellent results in the present example. Abstract : Environmental response effects of microsolvated methylene‐cyclopropene are studied through subsystem time‐dependent density‐functional theory. Various embedding methods are used in order to disentangle solvent effects with special focus on solvent response couplings. Understanding of both the physical processes as well as certain methodological advantages will pave the way for future approximations.